Depresi, Kecemasan, Stres dan Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Evelyn Hemme Tambunan; Ernawaty Siagian (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Hemodialysis is a therapy for patients with chronic renal failure, where depression, anxiety and stress are psychological reactions that are often experienced. This condition can affect the patient's quality of life. This study aims to determine the relationship between depression, anxiety and stress with the quality of life of chronic renal failure patients undergoing hemodialysis.The research design used in this study was analytic observational with a cross sectional approach. The study was conducted in October-December 2022 in the hemodialysis unit at one of the private hospitals in Bandar Lampung. 57 patients with chronic renal failure were willing to become respondents according to the inclusion criteria. DASS-42 questionnaire was used to measure depression, anxiety and stress and WHOQOL-BREF was used to measure quality of life. The results showed 8.8%, 43.8%, 10.5% and 7.2% of chronic kidney failure patients undergoing hemodialysis experienced depression, anxiety, stress and quality of life. Statistical data using logistic regression obtained the results of p=0.028, p=0.002, p=0.035. There is a relationship between depression, anxiety and stress with the quality of life of renal failure patients undergoing hemodialysis. It is necessary to consider a larger sample size and explore more deeply related to depression, anxiety and stress in GGK patients undergoing hemodialysis. Keywords: Depression, Anxiety, Stress, Quality Of Life, Crf Patients, Hemodialysis ABSTRAK Hemodialisis merupakan terapi bagi pasien yang mengalami gagal ginjal kronik, dimana depresi, kecemasan dan stres merupakan reaksi psikologis yang sering dialami. Kondisi ini dapat mempengaruhi kualitas hidup pasien. Penelitian ini bertujuan untuk mengetahui hubungan antara depresi, kecemasan dan stres dengan kualitas hidup pasien gagal ginjal kronik yang menjalani hemodialisa. Desain penelitian yang digunakan dalam penelitian ini adalah observasional analitik dengan pendekatan cross sectional. Penelitian dilakukan pada bulan Oktober-Desember 2022 di unit hemodialisa di salah satu rumah sakit swasta di Bandar Lampung. 57 pasien gagal ginjal kronik bersedia menjadi responden sesuai kriteria inklusi. Kuesioner DASS-42 digunakan untuk mengukur depresi, kecemasan dan stres dan WHOQOL-BREF digunakan untuk mengukur kualitas hidup. Hasil penelitian menunjukkan 8,8%, 43,8% , 10,5% dan 7,2% pasien gagal ginjall kronik yang menjalani hemodialisa mengalami depresi, kecemasan, stres dan kualitas hidup. Data statistik menggunakan regresi logistik didapatkan hasil nilai p=0,028, p=0,002, p=0,035. Terdapat hubungan antara depresi, kecemasan dan stres dengan kualitas hidup pasien gagal ginjal yang menjalani hemodialisa. Perlu untuk mempertimbangkan jumlah sampel yang lebih besar dan menggali lebih dalam terkait depresi, kecemasan dan stres pada pasien GGK yang menjalani hemodialisa. Kata Kunci: Depresi, Kecemasan, Stres, Kualitas Hidup, Pasien GGK, Hemodialisa